Synthesis and Cytotoxicity Assessment of Novel 7-O- and 14-O-Derivatives of Glaucocalyxin A - Liu, Hong-Chuan; Qiao, Li-Ming; Zheng, Wei; Xiang, Zhao-Bao; Chen, Hai-Sheng; Yu, Shi-Chong; Zhang, Da-Zhi; Wang, Ting; Zhang, Yue-Fan; Jin, Yong-Sheng (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Rabdosia japonica has been historically used in China as a popular folk medicine for the treatment of cancer, hepatitis, and gastricism. Glaucocalyxin A (GLA), an ent-kaurene diterpene isolated from Rabdosia japonica, is one of the main active ingredients showing potent inhibitory effects against several types of tumor cells. To the best of our knowledge, studies regarding the structural modification and Structure- Activity Relations (SAR) of this compound have not yet been reported. Objective: The aim of this study was to discover more potent derivatives of GLA and investigate their SAR and cytotoxicity mechanisms. Methods: Novel 7-O- and 14-O-derivatives of GLA were synthesized by condensation of acids or acyl chloride. The anti-tumor activities of these derivatives against various human cancer cell lines were evaluated in vitro by MTT assays. Apoptosis assays of compound 17 (7,14-diacylation product) were performed on A549 and HL-60 cells by flow cytometry and TUNNEL. The acute toxicity of this compound was tested on mice, at the dose of 300mg per kg body weight. Results: Seventeen novel 7-O- and 14-O-derivatives of GLA (1-17) were synthesized. These compounds showed potent cytotoxicity against the tested cancer cell lines, and almost all of them were found to be more cytotoxic than GLA and oridonin. Of the synthesized derivatives, compound 17 presented the greatest cytotoxicity, with IC50 values of 0.26μM and 1.10μM in HL-60 and CCRF-CEM cells, respectively. Furthermore, this compound induced weak apoptosis of A549 cells but showed great potential in stimulating the apoptosis of HL- 60 cells. Acute toxicity assays indicated that compound 17 is relatively safer. Conclusion: The results reported herein indicate that the synthesized GLA derivatives exhibited greater cytotoxicity against leukemia cells than against other types of tumors. In particular, 7,14-diacylation product of GLA was found to be an effective anti-tumor agent. However, the cytotoxicity mechanism of this product in A549 cells is expected to be different than that in other tumor cell lines. Further research is needed to confirm this hypothesis.
Keywords: cytotoxicity